LOGISTICS MANAGEMENT OF MOTOR VEHICLE TERMINAL OPERATIONS AS A QUEUING SYSTEM - Muzykin, M. I.; Nesterenko, H. I.; Bibik, S. I.; Barkalova, N. O. (Systems and Technologies, 2026)
The article analyzes calculating the motor vehicle terminal operations as a queuing system and determining the effectiveness of proposed methods for optimizing terminal operations based on logistic approaches. The research assesses the feasibility of implementing a control system at a humanitarian aid warehouse that would ensure the collection and storage of data on vehicle locations at loading areas, the status of loading and unloading mechanisms, and decision-making regarding their use, as well as to transmit commands to drivers to enhance the efficiency of road transport operations during humanitarian cargo delivery. The core principle of the terminal’s operations is optimal logistics management of cargo flows. Goods are sorted by priority and destination, ensuring minimal delays and rapid delivery of humanitarian aid to those in need. Calculations have been made for the operation of the motor vehicle terminal as a queuing system, specifically focusing on vehicle downtime during unloading at the humanitarian warehouse. The effectiveness of the proposed terminal optimization methods based on logistic approaches was also evaluated. The vehicle idle time during cargo operations was determined for traditional technology and for the implementation of a regulation system for truck arrival at loading fronts. Furthermore, the annual cost savings achievable through the organization of an optimal regulation system for truck arrivals at terminal loading fronts were calculated. It is proposed to develop the integrated decision support within the terminal system’s functional cycle as an automated system. The main objective of this method is to eliminate the ‘human factor,’ as automation is intended to enhance data quality, streamline the processing of cargo owner information, and optimize technological processes. The primary challenges for humanitarian aid terminals include ensuring cargo security, preventing delays, and maintaining operational responsiveness to changing conditions. At the same time, investments in advanced technologies and infrastructure improvements can significantly increase the operational efficiency of such terminals.